Isoleucine Enhances Plant Resistance Against Botrytis cinerea via Jasmonate Signaling Pathway - Li, Yuwen; Li, Suhua; Du, Ran; Wang, Jiaojiao; Li, Haiou; Xie, Daoxin; Yan, Jianbin (Frontiers in Plant Science, 2021)
Amino acids are the building blocks of biomacromolecule in organisms, among which isoleucine is the precursor of JA-Ile, an active molecule of phytohormone jasmonate. Jasmonate is essential for diverse plant defense responses against biotic and abiotic stresses. Botrytis cinerea is a necrotrophic nutritional fungal pathogen that causes the second most severe plant fungal disease worldwide and infects more than 200 kinds of monocot and dicot plant species. In this study, we demonstrate that isoleucine application enhances plant resistance against Botrytis cinerea in Arabidopsis, which is dependent on the JA receptor COI1 and the jasmonic acid-amido synthetase JAR1. The mutant lib with higher isoleucine content in leaves exhibits enhanced resistance to Botrytis cinerea infection. Furthermore, we found that the exogenous isoleucine application moderately enhanced plant resistance to Botrytis cinerea in various horticultural plant species, including lettuce, rose and strawberry, suggesting a practical and effective strategy to control Botrytis cinerea disease in agriculture. These results together showed that the increase of isoleucine could positively regulate the resistance of various plants to Botrytis cinerea by enhancing jasmonate signaling, which would offer potential applications for crop protection.